2014
DOI: 10.1136/acupmed-2013-010480
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Acupuncture during Pregnancy: A Systematic Review

Abstract: ObjectiveAlthough there is a growing interest in the use of acupuncture during pregnancy, the safety of acupuncture is yet to be rigorously investigated. The objective of this review is to identify adverse events (AEs) associated with acupuncture treatment during pregnancy.MethodsWe searched Medline, Embase, Cochrane Central Register of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Allied and Complementary Medicine Database (AMED) and five Korean databases up to February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 50 publications
(77 reference statements)
3
67
0
8
Order By: Relevance
“…However, it is important to report upon the trends that were noted on data extraction to help aid clinicians and patients on informed consent. Transient and non-serious adverse events were the norm in the included studies, and no adverse events were recorded as having an effect on the fetus, which supports a previous review [8]. The non-serious events were very similar in both acupuncture and non-acupuncture groups, which tentatively suggests that their occurrence is neither more nor less when receiving a skin-penetrating needle compared with another intervention.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, it is important to report upon the trends that were noted on data extraction to help aid clinicians and patients on informed consent. Transient and non-serious adverse events were the norm in the included studies, and no adverse events were recorded as having an effect on the fetus, which supports a previous review [8]. The non-serious events were very similar in both acupuncture and non-acupuncture groups, which tentatively suggests that their occurrence is neither more nor less when receiving a skin-penetrating needle compared with another intervention.…”
Section: Discussionsupporting
confidence: 79%
“…The range of adverse events that may be associated with acupuncture and moxibustion during pregnancy has recently been reviewed [8]; however, the definition of acupuncture was unclear, and no comparison was made between adverse events in acupuncture and non-acupuncture groups. Despite this recent review [8], the quality of reporting has yet to be established. In addition, the types, severity and occurrence of adverse events associated with a skin-penetrating needle compared with non-skinpenetrating interventions remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, considera-se que embora não tenham sido apresentadas complicações relacionadas à acupuntura, a literatura clássica deve ser levada em consideração 10 .…”
Section: Discussionunclassified
“…28 In this review, no studies reported information regarding AEs. Although existing studies regarding acupuncture for various conditions have supported the assertion that it is a relatively safe treatment modality, 29 acupuncture treatment varies considerably and is not without risk. 30 Future clinical trials must identify potential AEs more thoroughly.…”
Section: Implications For Researchmentioning
confidence: 99%